Composição e estrutura trófica da ictiofauna de piscinas de maré da Praia do Paiva, região metropolitana do Recife-PE - Dantas, Rafael dos Santos (2013)
The Praia do Paiva, sparsely inhabited and conserved, is located in the municipality of Cabo de Santo Agostinho, metropolitan area of Recife, the capital of Pernambuco State, Brazil, and is inserted in a region under the influence of great human interference, either derived from tourism, or the Port of Suape. This study has investigated the composition and trophic structure of recifal fish fauna in five tidepools on Praia do Paiva. In a total of 75 visual censuses conducted in transects, and intensive searches conducted in the area, 66 species belonging to 34 families were recorded. The pools shared 32.60% of species whose distribution is known along the Western Atlantic. No significant differences were observed between the diversity and richness recorded in the pools. However, this difference was observed between pools versus evenness. Predators of Mobile Invertebrates, Territorial Herbivores, Omnivores, Not Territorial Herbivores, Predators of Sessile Invertebrates, Zooplanctívoros, Generalists Carnivores and Piscivores were the regsitred trophic categories. The results of this work shows that coverage of the substrate does not differs significantly between the study areas, probably due to the proximity of the pools, which are subject to the same environmental factors. The area has a greater diversity of fish than many reef environments along the Brazilian coast, highlighting its importance. The species showed no clear difference in the use of environments, having distribution associated with intermediate values of environmental variables. The distribution of trophic categories follows a pattern known in the literature, which has Predators of Mobile Invertebrates as the most abundant category. The uses of the pools by tourists and fishermen was recorded in the study area, in addition to impacts from construction on the shoreline, which can lead to a decrease in the diversity of fish in the study area. The results of this study may support future evaluation of the condition of the fish fauna associated to tidepool environments at Praia do Paiva.